Environmental Effect on the Growth and Enzyme Activity of Fucoidanase-Producing Bacteria Cytobacillus kochii GSD - Setyawan, Agus; Amiin, Muhammad Kholiqul; Fidyandini, Hilma Putri; Lahay, Almira Fardani; Yusup, Maulid Wahid; Nurhalisa, Alifia Adibila; Saputra, Rizqy Hadi; Putri, Wanda Andella; Ratna Juliasih, Ni Luh Gede; Rivaie, Arief Rahman; Saputra, Suryadi (Faculty of Fisheries and Marine Universitas Airlangga, 2025)
Graphical Abstract Highlight Research 1. Sargassum polycystum has been extracted and analyzed. 2. Cytobacillus kochii GSD in response to fucoidanase-producing enzyme activity was analyzed. 3. Optimum temperature, pH, and salinity can suppress the activity of the fucoidanase enzyme through the inhibition test. 4. Cytobacillus kochii GSD can produce fucoidanase enzyme with low molecular weight. Abstract Extensive research has shown that low molecular weight fucoidan exhibits significantly greater biological activity than its high molecular weight. C. kochi GSD, a Sargassum symbiont bacterium, is proven to have the activity of hydrolyze fucoidan. This study proposes the growth optimization and fucoidanase enzymatic activity of C. kochii GSD bacteria under varying environmental conditions (temperature, pH, and salinity) cultured in basic liquid medium (BLM) for 48 hours. Based on Response Surface Methodology (RSM), the range of temperature, pH, and salinity for the growth optimization test of C. kochi GSD bacteria were 26.591, 30, 35, 40, and 43.49oC, the pH used starts from 3.636, 5, 7, 9, and 10.363, while the salinity to be used starts from 3.522, 5, 17.5, 30, and 38.522 ppt, respectively. The best conditions for growth of each environment were then continued with the test of fucoidanase enzyme activity in vitro. The results showed that C. kochii GSD bacteria grew optimally at temperature, pH, and salinity of 35oC, 7, and 30 ppt, respectively. The optimum enzyme activity of C. kochii GSD is at 72 hours with the forming of clear zones on media containing fucoidan and given Cetylpyridinium chloride (CPC) solution with clear zone diameters of 31.17 mm (temperature), 25.9 mm (pH), and 20.97 mm (salinity), respectively. The conclusion of this study is a high novelty finding to produce low molecular weight fucoidan enzymatically with C. kochii GSD bacteria to be used as an immunostimulant.